Los mayordomos de fábrica y la economía de quince parroquias de la Diócesis de Antioquia, 1825-1842 (2009)
ABSTRACT: This paper examines the workings of the factories of 15 parishes of the First Diocesis of Antioquia, between 1825 and 1842, a period in which the Colombian state controlled parish finances. The motives and scope of this close governmental control are analysed, and special attention is paid to the figure of the mayordomo de fábrica, at that time the principal person responsible for the administration of parish economies. The supervisor administered parish finances, procured elements required in religious ceremony, ensured priests were adequately equipped and dressed, and looked after church maintenance. Based on the wealth of information available from the accounts books of the mayordomo de fábrica, held by the Historical Archives of Antioquia, the paper analyses the main sources of parish income and expenditure in this region of Antioquia.